2013
DOI: 10.3390/ijms140917845
|View full text |Cite
|
Sign up to set email alerts
|

Icariin Protects Rat Cardiac H9c2 Cells from Apoptosis by Inhibiting Endoplasmic Reticulum Stress

Abstract: Endoplasmic reticulum stress (ERS) is one of the mechanisms of apoptotic cell death. Inhibiting the apoptosis induced by ERS may be a novel therapeutic target in cardiovascular diseases. Icariin, a flavonoid isolated from Epimedium brevicornum Maxim, has been demonstrated to have cardiovascular protective effects, but its effects on ERS are unknown. In the present study, we focused on icariin and investigated whether it might protect the cardiac cell from apoptosis via inhibition of ERS. In H9c2 rat cardiomyob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 35 publications
2
28
0
Order By: Relevance
“…As a natural prenylated flavonol glycoside, ICA has been shown to suppress the proliferation of various types of cancer cells [11][12][13][14]. Various molecules and signaling pathways are involved in the anti-tumor effects of ICA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a natural prenylated flavonol glycoside, ICA has been shown to suppress the proliferation of various types of cancer cells [11][12][13][14]. Various molecules and signaling pathways are involved in the anti-tumor effects of ICA.…”
Section: Discussionmentioning
confidence: 99%
“…Experimentally, ICA can induce apoptosis through a ROS/JNK-dependent mitochondrial pathway in human hepatoma SMMC-7721 cells [28]. Additionally, ICA can protect rat cardiac H9c2 cells from apoptosis by inhibiting ERS [14]. However, the role of ERS signaling in the anti-NSCLC activity of ICA has not been examined.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Interestingly, NAC, a scavenger of ROS, could also inhibit ER stress, suggesting that ROS accumulation could trigger ER stress. ROS is linked to ER stress in other systems, such as rat cardiac cells, and human hepatoma cells [33, 34]. Reports on the interactions between ROS and ER stress are still controversial and not clear [9, 35, 36].…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Song et al revealed that icariin reduced cardiac remodeling through down-regulating myocardial apoptosis and matrix metalloproteinase activity in rats with congestive heart failure [4]. Moreover, a recent in vitro study has shown that Icariin protects rat cardiac H9c2 cells from apoptosis by inhibiting endoplasmic reticulum stress [5]. These results suggested that icariin could exert cardioprotective effects.…”
Section: Introductionmentioning
confidence: 94%